1998
DOI: 10.1093/oxfordjournals.aje.a009470
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Diabetic Retinopathy in the Multiethnic Population of Mauritius

Abstract: This study examines the prevalence of, and risk factors for, diabetic retinopathy in Asian Indian, Chinese, and Creole Mauritians in whom there is an increasing prevalence of non-insulin-dependent diabetes mellitus (NIDDM). As part of a population-based survey on the Indian Ocean island of Mauritius in 1992, glucose tolerance was classified using a 75-g oral glucose tolerance test on 6,553 persons. Subjects with newly diagnosed (n = 358) or known diabetes (n = 388), and a random sample of one in four subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
2
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 31 publications
6
66
2
5
Order By: Relevance
“…In addition, small sample sizes and different grading criteria of DR in these three studies might be taken into consideration. Earlier studies have shown that age, 13,14 gender, 14,15 BMI, 16,17 WHR, 16 TC, 13 HDL-C, 18 LDL-C, 19 BUN, blood creatinine, 20 and UAER 21,22 have certain associations with DR in diabetics. However, in our study, it appears that those related above are not risk factors for DR in prediabetics.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, small sample sizes and different grading criteria of DR in these three studies might be taken into consideration. Earlier studies have shown that age, 13,14 gender, 14,15 BMI, 16,17 WHR, 16 TC, 13 HDL-C, 18 LDL-C, 19 BUN, blood creatinine, 20 and UAER 21,22 have certain associations with DR in diabetics. However, in our study, it appears that those related above are not risk factors for DR in prediabetics.…”
Section: Discussionmentioning
confidence: 96%
“…Diabetes duration has been shown to be an independent risk factor for retinopathy in many studies (11,21). Duration of diabetes reflects total glycemic control and risk factor exposure over time (7). Although C-peptide was lower in those with retinopathy than those without, its significance disappeared once duration of diabetes was added to the model.…”
Section: Methodsmentioning
confidence: 99%
“…Although C-peptide was lower in those with retinopathy than those without, its significance disappeared once duration of diabetes was added to the model. Hypertension has frequently been shown to be a risk factor in the development of retinopathy (7,10,31). In the present study, elevated SBP had an increasing impact with longer duration of diabetes and higher HbA 1c values (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…when the damaging effect on blood vessels and nerves has proceeded unnoticed for a long time. 50-70% of type 2 diabetes cases show DR symptoms after 10 years, and 90% of these patients after 30 years [4,5].Another complication leading to loss of sight is cataract. It is characterized by an opacification of the translucent media of the lens that progresses rapidly in diabetic patients.…”
mentioning
confidence: 99%